2012
DOI: 10.7554/elife.00090
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin blocks proliferation of cancer cells through proteolytic activation of CREB3L1

Abstract: Doxorubicin is used extensively for chemotherapy of diverse types of cancer, yet the mechanism through which it inhibits proliferation of cancer cells remains unclear. Here we report that doxorubicin stimulates de novo synthesis of ceramide, which in turn activates CREB3L1, a transcription factor synthesized as a membrane-bound precursor. Doxorubicin stimulates proteolytic cleavage of CREB3L1 by Site-1 Protease and Site-2 Protease, allowing the NH2-terminal domain of CREB3L1 to enter the nucleus where it activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 35 publications
4
111
2
2
Order By: Relevance
“…In addition, the same group demonstrated that CREB3L1 expression was required for the activation of p21 by the chemotherapy agent doxorubicin, preventing the proliferation of cancer cells. In cells lacking CREB3L1, the effectiveness of doxorubicin was decreased (51). In addition, CREB3L1 silencing through a chromosome fusion is associated with low-grade fibromyxoid sarcoma (42).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the same group demonstrated that CREB3L1 expression was required for the activation of p21 by the chemotherapy agent doxorubicin, preventing the proliferation of cancer cells. In cells lacking CREB3L1, the effectiveness of doxorubicin was decreased (51). In addition, CREB3L1 silencing through a chromosome fusion is associated with low-grade fibromyxoid sarcoma (42).…”
Section: Discussionmentioning
confidence: 95%
“…One of the transcription factors most highly up-regulated in FLHCC (SI Appendix, Table S10) is cAMP responsive element binding protein 3-like 1 (CREB3L1), which is also a target of PKA. CREB3L1 induces expression of genes involved in extracellular matrix production (49), and CREB3L1 activity has also been reported to be an indicator of tumor cells that are sensitive to doxorubicin (50). PKA directly phosphorylates CREB (24).…”
Section: Resultsmentioning
confidence: 99%
“…Denard et al, showed that during virus infection, Creb3L1 is activated and functions to increase transcription of cell cycle inhibitors and to block expression of factors that promote cell proliferation (Denard et al, 2011). The same group has also shown that cancer cells expressing Creb3L1 are more sensitive to treatment with the chemotherapeutic agent doxorubicin (Denard et al, 2012). Cancer cell lines that express Creb3L1, when treated with doxorubicin, undergo RIP, activating Creb3L1 and increasing the expression of cell cycle inhibitor genes, again preventing cell proliferation.…”
Section: Creb3l1/oasismentioning
confidence: 99%
“…Cancer cell lines that express Creb3L1, when treated with doxorubicin, undergo RIP, activating Creb3L1 and increasing the expression of cell cycle inhibitor genes, again preventing cell proliferation. These studies suggest that tumors with high levels of Creb3L1 expression are more likely to respond to treatment with doxorubicin than those that do not express Creb3L1 (Denard et al, 2012). In mammary cancer lines, Creb3L1 is downregulated in highly metastatic cancers (Mellor et al, 2013).…”
Section: Creb3l1/oasismentioning
confidence: 99%